Pengaruh Jumlah Kunjungan Wisatawan Terhadap Penerimaan Pajak Hotel, Pajak Restoran Dan Pendapatan Asli Daerah - Widyaningsih, Putu; Kembar Sri Budhi, Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
This research is aimed to determine number of the visitors  towardsRevenue (PAD) of Gianyar Regency,in a direct manner  whether  is not direct manner. In this results influence is not direct manner the number of tourists towards Revenue (PAD) by means of hotel tax revenues and restaurant tax revenues. This research is using secondary data, then analyzed by path method. The results showed  the number of tourists visit is a not significant infliencesin a direct manner towards Revenue (PAD). However is not direct mannersignificant  influencesby mean of hotel tax revenues and restaurant tax revenues.
Keywords: the number of tourists visiting; hotel tax; restaurant tax; revenue.